2020
DOI: 10.5465/annals.2018.0014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mandatory and Voluntary Regulatory Pressures on Firms’ Environmental Strategies: A Review and Recommendations for Future Research

Abstract: This paper presents an in-depth review of scholarship on how mandatory and voluntary regulatory pressures on firms affect their environmental strategies and performance. While mandatory regulation typically has a strong and positive influence on firms' environmental performance, studies of the effects of voluntary pressures demonstrate that by themselves they are unlikely to bring about significant improvement in environmental outcomes. Accordingly, future research should focus on the complementary impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(187 citation statements)
references
References 131 publications
4
177
0
6
Order By: Relevance
“…Finally, we note that most previous studies treat the adoption of ISO 14001 as a binary choice (Aragón‐Correa et al, 2020). This treatment has been recently challenged by several authors who argue that there are differences in the scope of ISO 14001 adoption among firms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, we note that most previous studies treat the adoption of ISO 14001 as a binary choice (Aragón‐Correa et al, 2020). This treatment has been recently challenged by several authors who argue that there are differences in the scope of ISO 14001 adoption among firms.…”
Section: Discussionmentioning
confidence: 94%
“…Our main independent variable is ISO , which is measured as the percentage of facilities of a firm that have ISO 14001 certification; that is, the variable ISO ranges from 0 for firms without any certified facility to 100 for firms in which all facilities are certified with the environmental standard. To our knowledge, this measure is a novelty in the literature, as most studies identify the adoption of ISO 14001 with dichotomous variables only (Aragón‐Correa, Marcus, & Vogel, 2020).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Researchers have recognized the role of regulatory bodies in initiating environmental response for firms [8,9,31,32]. Comprehensive environmental strategies by organizations are more common in industries that face stricter environmental regulations [8].…”
Section: Regulatory Bodies' Concernmentioning
confidence: 99%
“…Similarly, regulatory intensity and institutional pressure have forced firms to be environmentally responsive [31,32,34]. After studying the environmental performance of 14 paper and pulp mills in Australia, New Zealand, British Columbia in Canada, and the states of Washington and Georgia in the USA, Kagan et al [36] have found that regulatory requirements play an important role in improving the environmental response of firms.…”
Section: Regulatory Bodies' Concernmentioning
confidence: 99%
“…The literature has examined, for example, the role of nonfinancial reporting standards and their design (e.g., Grushina, 2017; Rawhouser et al, 2018). Other studies have shown a potential consolidation in the very diverse nonfinancial disclosure landscape where voluntary guidelines exist alongside mandatory reporting regimes (e.g., Aragòn-Correa et al, 2020; Eberlein, 2019). Research has also critically examined how national standards coexist and compete with international frameworks (e.g., Einwiller et al, 2016).…”
Section: Topic Of the Special Issuementioning
confidence: 99%